MODERN METHODS OF DIAGNOSING AND TREATING NEUROLOGICAL CHANGES OBSERVED IN ALCOHOLISM - Shuxrat Toshtemirovich, Niyozov; Mavludaxon Mirxamzayevna, Mamurova; Bobir Temirpulotovich, Turayev (PT. Antis International Publisher, 2025)
Objective: This study aims to explore modern methods of diagnosing and treating neurological changes associated with alcoholism, with a focus on understanding the pathological mechanisms underlying alcohol dependence and its impact on the nervous system. Method: A systematic review of recent clinical studies, diagnostic criteria from DSM-5, and neuroimaging techniques was conducted to evaluate current diagnostic tools and therapeutic approaches. The analysis included neuropsychological assessments, biomarker identification, and pharmacological interventions targeting alcohol-induced neurological impairments. Results: Findings indicate that advanced neuroimaging techniques, such as MRI and PET scans, along with neurocognitive testing, are effective in detecting alcohol-related neurological damage. Pharmacological treatments, including the use of naltrexone, acamprosate, and disulfiram, combined with cognitive-behavioral therapy, show significant efficacy in managing alcohol cravings and mitigating neurological deterioration. Novelty: This study highlights the integration of neuroimaging biomarkers with personalized pharmacological and behavioral interventions as a novel approach for improving diagnostic accuracy and treatment outcomes in patients with alcohol-related neurological changes.